MINDFULNESS VS. OVERTHINKING: A TRANSPERSONAL AND PSYCHODIAGNOSTIC APPROACH TO COLLEGE STUDENTS' MENTAL HEALTH - Sugesti, Eka; Iskandar Dinata, Konto (International Journal of Multidisciplinary Reseach, 2025)
This study employs a qualitative approach using a literature review method to examine the role of mindfulness in addressing overthinking and improving university students’ mental health. Based on an analysis of various scholarly sources and previous studies, mindfulness is found to be effective in reducing anxiety, enhancing emotional regulation, and helping students observe their thoughts without becoming trapped in excessive rumination. Mindfulness practices also enable individuals to be more present in the moment, allowing them to respond to academic pressures in a more adaptive manner. When combined with a transpersonal approach, the benefits of mindfulness expand further by fostering self-awareness, spiritual growth, and holistic psychological balance. The transpersonal perspective supports students in understanding deeper inner experiences and strengthening connections with positive values that promote mental well-being. In light of these findings, this study recommends that universities integrate mindfulness practices into mental health programs, counseling services, and student development activities. Such efforts are considered valuable in helping students cope with increasingly complex academic demands, enhance their resilience, and create a healthier, more supportive learning environment for their overall mental well-being.